Factors influencing the development of a Thai health-promoting faculty of nursing: An ethnographic exploration - Sirakamon S. (2014)
Universities can make a significant contribution to improve population health through encouraging faculty members and universities to focus on health promotion, using a health-promoting framework. This qualitative study explored factors influencing the development of a health-promoting nursing faculty in a Thai university. Data were collected via in-depth interviews of 15 nursing academics and four academic support staff, and fieldwork observations. Data were analyzed using Spradley's ethnographic approach. Findings included informants perceiving that the achievement of a health-promoting educational organization is dependent on a number of contexts, including the presence of the national health policy regarding health promotion, the policies and actions of a university, faculty administrative contexts, organizational culture, ThaiHealth actions and support, profession-related factors, time limitations, the physical environment, and personal factors. Moreover, the development of health-promoting faculty within nursing should be based on the existing support in a university and faculty. Factors impeding such development must determine whether health promotion and well-being are to be achieved as a foundation for faculty work, and the mission of a university within a healthy settings approach. © 2011 Blackwell Publishing Asia Pty Ltd..